Restaurant pre-ordering system: an approach to channeling dynamic business creativity - Anuar, Sazly; Abdullah, Salfarina; Soon, Joon Wai (Research India Publications, 2017)
Technological advancement has led to the incorporation of information systems onto human daily life activities. Computer systems have helped improve the modern human lifestyle by simplifying and easing the execution of activities like writing a letter, watching a movie, and even grocery shopping. Nowadays, change has been seen on the ways of ordering at restaurants from the conventional paper orders to on line ordering through the internet. Therefore, in effort to enhance and optimize the current ordering mechanism, we develop a restaurant pre-ordering system that allows customers to order in advance prior to arriving physically at selected restaurants. This will help reduce the waiting time needed for the preparation of meals and help improve the table turnover rates at restaurants. Besides that, we also provide assistance for tourists and travelers in search for local delicacies during their travel to our country. The fact that not many tourists have decent understanding of our national language, Bahasa Malaysia makes the searching for local food a rather difficult thing to do.Therefore, by having a smart search function which allows searching through image and speech, this system can greatly elevate the difficulties and troubles faced by tourists and travelers during their search for local food here in Malaysia.